Anxiety sensitivity moderates drug cravings in response to induced negative affect in opioid dependent outpatients. (September 2018) - Stathopoulou, Georgia; Pollack, Mark H.; Otto, Michael W.
Highlights: Anxiety Sensitivity significantly moderated drug cravings in response to negative affect induction. Only among individuals with high anxiety sensitive scores, anxiety sensitivity moderated drug cravings. Coping motives did not significantly predict drug cravings in response to negative affect induction.